What kind of future of interspecies relations are we heading for? - Lange, Łucja (W poszukiwaniu zielonego ładu, 2022)
The chapter discusses in four steps the way to consciously build a multi-species city. Starting with how the cities look like today—aesthetically covered with concrete, unfavorable to any living organisms, but seemingly easy to maintain and clean, the author goes on to the memories of cities from years ago, in which nature played a large role, and its protection was one of the overarching goals. Then she moves on to how could we consciously cohabit and wisely create common spaces, and then she draws attention to the aspect of non-harm, which should guide all attempts to build multi-species communities.